1993
DOI: 10.1177/026540759301000205
|View full text |Cite
|
Sign up to set email alerts
|

Shared Activities and Marital Satisfaction: Causal Direction and Self-Expansion versus Boredom

Abstract: Fifty-three married couples were randomly assigned to engage in activities for 1.5 hours each week for 10 weeks that were self-defined as (a) exciting or (b) pleasant, or couples were in a (c) no-special-activity control group. Pretest and post-test data were obtained on a standard marital satisfaction measure (adjusted for scores on a social desirability index). A planned linear contrast comparing the two activities groups to the control group was not significant and had a small effect size; thus the theory t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
164
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(175 citation statements)
references
References 13 publications
9
164
1
1
Order By: Relevance
“…In turn, the experience of self-expansion in an established relationship motivates continued maintenance and development of the relationship (Lewandowski & Aron, 2004;Lewandowski, Aron, Bassis, & Kunak, 2006). Evidence suggests that in addition to providing resources, the experience of self-expansion produces positive effect, which may translate into relationship satisfaction (Reissman, Aron, & Bergen, 1993). Further, on their self-expansion questionnaire (SEQ), Aron (2002, 2004) Self-Expansion through Characters 557…”
Section: The Motivation For Self-expansion and Achieving Possible Selvesmentioning
confidence: 99%
“…In turn, the experience of self-expansion in an established relationship motivates continued maintenance and development of the relationship (Lewandowski & Aron, 2004;Lewandowski, Aron, Bassis, & Kunak, 2006). Evidence suggests that in addition to providing resources, the experience of self-expansion produces positive effect, which may translate into relationship satisfaction (Reissman, Aron, & Bergen, 1993). Further, on their self-expansion questionnaire (SEQ), Aron (2002, 2004) Self-Expansion through Characters 557…”
Section: The Motivation For Self-expansion and Achieving Possible Selvesmentioning
confidence: 99%
“…In their review of the literature on marriage Reissman, Aron, and Bergen (1993) concluded that the time couples spent engaging in leisure activities, such as talking or sharing tasks, was related to their relational satisfaction. Similarly, Vangelisti and Banski (1993) found that couples who talked at the end of the workday had higher levels of satisfaction than those who did not spend nightly time interacting with one another.…”
Section: Frequency Of Casual Interactionmentioning
confidence: 99%
“…Reissman et al (1993) found that when compared to pleasant activities, the pursuit of exciting activities led to a greater increase in marital satisfaction. This finding implies that wives' shared activities with their pastorhusbands are not exciting enough to affect their marital satisfaction.…”
Section: Doing Things Togethermentioning
confidence: 99%